Plasmodium falciparum infection and naturally acquired immunity to malaria antigens among Ghanaian children in northern Ghana - Seidu, Z.; Lamptey, H.; Whittle, N.O.; et al. (Parasite Epidemiology and Control, 2023)
Background: The surge in malaria cases and deaths in recent years, particularly in Africa, despite the widespread implementation of malaria-control measures could be due to inefficiencies in malaria control and prevention measures in malaria-endemic communities. In this context, this study provides the malaria situation report among children in three Municipalities in Northern Ghana, where Seasonal Malaria Chemotherapy (SMC) is implemented by Ghana Health Service (GHS). Methods: A cross-sectional household survey was carried out to assess the malaria knowledge, attitudes, and practices (KAP) and malaria prevalence in 394 households in 13 rural communities in the Kumbugu, Nanton and Tolon Municipalities, Northern Region, Ghana. This was followed by screening for P. falciparum infection with anti-HRP2 RDT and PCR among children 1–17 years in the households. Plasma levels of IgG specific for crude P. falciparum antigen (3D7) and four re combinant malaria antigens (CSP, GLURP, MSP3, and Pfs230) were assessed by ELISA. The malaria and parasitaemia data were converted into frequency and subgroup proportions and disaggregated by study sites and demographic information of the participants. The ELISA data was converted to arbitrary units (AU) and similarly compared across study sites and demographic information. Results: The P. falciparum infection rate and frequency of malaria were high in the study areas with significant age-dependent and inter-community differences, which were reflected by differences in plasma levels of P. falciparum-specific IgG. Over 60% of households reported the use of bed nets and indoor insecticide sprays/coils, and 14% mentioned bush clearing around homes (14%) as malaria preventive measures. Community health centres were the preferred place for households (88%) to seek malaria treatment but over-the-counter drug stores were the major source (66%) of their antimalarials. Overall, malaria preventive and treatment practices were sub-optimal. Conclusions: P. falciparum infection and malaria are still high in the studied communities, indi cating that preventive and control measures against the disease in the region remain inadequate. Efforts to ensure high SMC compliance and to improve preventative and treatment practices thus seem cost-beneficial “low-hanging fruits” in the fight against malaria in the Northern Region of Ghana.
Research Article
Keywords: Seasonal malaria chemotherapy (SMC); Plasmodium falciparum; Malaria